برصغیر کی اردو تفاسیر پر تفسیر روح المعانی کے صوفیانہ اثرات - Ali, Murad; Hussain, Dr. Muhammad Imtiaz (Al-Irfan, 2022)
The Holy Quran is Allah Almighty’s final message for mankind. It is a complete guideline in every age till the day of judgement. The Allah Almighty bestowed this Ummah with capable exaggerators of Quran who have tried to make this book understandable for common Muslims. Some of those exaggerators’ work is commendable that lasted its great impact on others. Such great name is Sayyad Mahmood Aalusi who wrote ‘Tafseer Rooh ul Muaani’ during the period of 1252hj – 1267hj. This exaggeration is very comprehensive interpretation of Holy Quran in 30 volumes. It provides detailed notes on problems based on surf, nahv, Faith, Fiqh and Sufism discussed in Holy Quran. It influenced exaggerators came after him so the Urdu exaggerations of subcontinent too. In this article it is showed that Urdu exaggerations in subcontinent were influenced by Tafseer Roh ul Muaani. I have focused on interpretations related to Sufism. I have given many examples in this regard.